PEDAGOGICAL DIAGNOSIS AS A MEANS OF DEVELOPMENT CREATIVE ABILITIES OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2007)
In article problems of pedagogical diagnostics, and influence on development of creative abilities of students are considered during training in the higher school.